Design thinking application methodology for pediatric service innovation - Serrano Cárdenas, Lizeth Fernanda; Bravo Ibarra, Edna Rocío; Díaz Piraquive, Flor Nancy; Rozo-Rojas, Ivanhoe; González-Crespo, Rubén; Calvo, Ana (Communications in Computer and Information Science, 2020)
Design Thinking is defined as a methodology that facilitates the generation and implementation of innovative ideas contributing to competitiveness in the current dynamic context. The aim of this article delves into the concept of Design Thinking, its potential application in the health sector and presents a methodology designed from theoretical contributions for innovation in the service experience of pediatric patients in a hospital. The present study shows excellent results about the implementation of Design Thinking in the Health Sector, specifically in a Pediatric Department. The contribution of the Design Thinking methodology was the Hospital Classrooms and the development of a videogame for the understanding of Acute Lymphoid Leukemia that could help the wellness and the quality of life of pediatric patients.
Ponencia de la Conferencia "13th International Conference on Knowledge Management in Organizations, KMO 2018; Zilina; Slovakia; 6 August 2018 through 10 August 2018"
Keywords: design thinking; health; innovation; service experience; Scopus(2); WOS(2)